A systematic review on the current status of PSMA-targeted imaging and radioligand therapy - Capasso, Giuseppe; Stefanucci, Azzurra; Tolomeo, Anna (European journal of medicinal chemistry, 2024)
Prostate specific membrane antigen (PSMA) has been the subject of several studies in recent decades as a promising molecular target for prostate cancer (PCa), in fact it is considered an excellent molecular target for both PCa imaging (both for staging and follow-up), by means of PET/CT and for radioligand therapy. Its interesting molecular features have enabled the development of a new diagnostic and therapeutic approach for PCa, called "theranostics." Considering the abundance of PSMA-based probes that have appeared so far in the literature, the present work focuses the attention on radiopharmaceuticals with increasing clinical application, highlighting advantages and disadvantages in terms of different metabolization and excretion processes, pharmacokinetic, binding affinity and variable internalization rate, tumor-to-background ratio, residence times and toxicity profile.